Evil, Prayer and Transformation - Burns, Elizabeth (Open theology, 2020)
Analytic theodicy commonly suggests an overarching reason why a benevolent, omniscient and omnipotent deity permits the quantity and intensity of suffering in our world. This is often couched in terms of freedom of belief or action, or some other variation of the claim that suffering is "worth the price." I argue that not even the hope of post-mortem consolation could adequately compensate any individual for the inevitable loss of everything which makes, or might have made, life in this world worth living. By contrast, transformational theodicy argues that suffering is an unfortunate by-product of our evolving world. All living things are connected to other living things by means of networks, symbolised for John Hick by Indra’s Net. Divinity is both the force which brought about the beginning of the universe and sustains its continued existence and an objectively existing standard of goodness which is manifested in varying degrees throughout our world, metaphorically conceived in terms of non-binary personhood. It casts light on human endeavours and provides a source of power on which humankind may draw by means of prayer or meditation to influence the networks of living things in order to prevent or alleviate suffering and promote the flourishing of living beings.